Innovative Development: The Potential of Russian Science and Education - Vladimir A. Shamakhov (Евразийская интеграция: экономика, право, политика, 2019)
The questions connected with innovative development and potential of domestic science and education are considered in the article. Innovative development of Russia is based on the objective data characterizing a condition of innovative economy as bases of transition of Russia to new, sixth technological way. The questions connected with formation of an image of the future, geocultural values, a way of life and a view of the world around, the national purposes of development are analyzed in the article.